Pendampingan Pengukuran Efektivitas RAB dalam Perencanaan dan Pengendalian Keuangan TK-PPEG - Sari, Filma Alia; Siahaan, Nicholas Saputra; Manurung, Christian; Matondang, Rizky Noviana; Desmafitri, Elni; Gurning, Ririn Gohanna; Yusrah, Yusrah; Firani, Nydia Putri; Rizdajayanti, Aisara; Yelviani, Sri; Safitri, Ellin (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: In Siak District, Sumatra, 57.44% of the administrative area consists of peatlands. To address the environmental and agricultural challenges in this ecosystem, Penghulu of Dayun initiated the formation of the Peat Ecosystem Protection and Management Team of Kampung Dayun Lestari (TK-PPEG). This community-based, non-profit organization developed an Integrated Paludiculture Demonstration Plot as part of the Peat Care Independent Village initiative. This service program aimed to evaluate the effectiveness of financial planning and control in the development of this demonstration plot. Research methodology: The program employed a mentoring approach involving structured discussions, observations, and analyses. The activity focused on assessing the alignment between the proposed Budget Plan (RAB) and actual budget realization. Results: The analysis revealed that 60% of the total budget had been effectively realized, aligning with initial cost estimates and prevailing market prices. This indicates that the financial execution was efficient and well managed. The demonstration plot project is progressing smoothly, with the budget being strategically utilized and in line with planning expectations. Conclusions: The RAB proved to be an essential financial tool for guiding decisions regarding procurement and resource allocation. Its use ensures stakeholder involvement and contributes to financial control and goal achievement. The high alignment between the RAB and budget realization suggests strong planning and implementation. Limitations: The remote location of the demonstration site and limited observation time posed challenges in comprehensively monitoring the activities. Contribution: This program supports the improvement of financial management practices and enhances transparency and accountability within local environmental initiatives.